Extraction and isolation of kappa carrageenan from red seaweeds - Nur Nabillah, Mohd Arif (2014)
This works present the extraction and isolation process of kappa carrageenan from red seaweed. Product from this research can be use in pharmaceutical industry for production of capsule as it give advantages in aspect of economical, health and cultural. To extract and isolate kappa carrageenan, alkali treatment and alcohol precipitation was involved. In the alkali treatment of extraction process, three variables (i.e. temperature, concentration and time) have been investigated whereas in isolation process, isopropanol was used to study the separation of kappa carrageenan through precipitation. Based on experimental analysis, alkali treatments influence the yield, rheological and physichochemical properties of kappa carrageenan. Increasing potassium hydroxide (KOH) concentration decreased the yield and viscosity of kappa carrageenan due to degradation of polysaccharides. Temperature and time gave insignificant effect to the properties of extracted carrageenan. From the experimental result, the extraction and isolation of kappa carrageenan has been successfully conducted. Therefore, the range of concentration, temperature and time used in this analysis is acceptable to extracte and isolate kappa carrageenan